2020
DOI: 10.1007/s00264-020-04694-8
|View full text |Cite
|
Sign up to set email alerts
|

Supracondylar humerus fractures in low- and lower middle-income countries: a scoping review of the current epidemiology, treatment modalities, and outcomes

Abstract: Background The purpose of this scoping review was to examine the nature and quality of research regarding paediatric supracondylar humerus (SCH) fractures in low and lower middle-income countries (LICs). Methods We searched PubMed, Embase, Web of Science, and African Journals Online on January 9, 2018, for studies of SCH fractures in LICs. Studies were categorized by geographic region, Gartland classification of included patients, and study design. We evaluated each study's methodology and conclusions. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
(13 reference statements)
1
8
0
Order By: Relevance
“…In our cohort, 54% of the patients were boys, 75% of the patients had left-sided injuries, and 83% were injured by falling, all of which are similar to rates reported in the literature 19,25-30 . Delayed presentation among pediatric fracture patients has previously been reported to be as high as 28% in Malawi 17 .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In our cohort, 54% of the patients were boys, 75% of the patients had left-sided injuries, and 83% were injured by falling, all of which are similar to rates reported in the literature 19,25-30 . Delayed presentation among pediatric fracture patients has previously been reported to be as high as 28% in Malawi 17 .…”
Section: Discussionsupporting
confidence: 87%
“…S CHFs are common, but few studies have examined outcomes in low-and middle-income countries, where many patients are treated nonoperatively because of limited surgical capacity 19,25 . In our retrospective assessment of children with closed SCHFs treated nonoperatively at NKKDH in Malawi, we found that patients with Gartland type-II and III fractures had a significantly increased risk of clinical complications and functional impairment compared with patients with type-I fractures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These fractures are frequently neglected and thus present late, particularly in developing countries. 12 Many researchers have already expressed their opinion in favor of emergent treatment of these fractures in order to resist complications. 13 In this study, there were a total of 30 (71.4%) male and 12 (28.6%) female.…”
Section: Discussionmentioning
confidence: 99%
“…In countries with poor medical infrastructure and limited staff and resources, the humeral patella fractures in children under 16 are in the first place. In this context, the orthopedic treatment of fractures with surgery reccomendation leads to a large number of complications [1,2]. Salter-Harris type II fractures are low fractures, infracondylar, transphyseal fractures and involves the growth cartilage.…”
Section: Introductionmentioning
confidence: 99%